2023
DOI: 10.1126/sciadv.adh4168
|View full text |Cite
|
Sign up to set email alerts
|

Solid-state NMR structure determination of a membrane protein in E. coli cellular inner membrane

Huayong Xie,
Yongxiang Zhao,
Weijing Zhao
et al.

Abstract: Structure determination of membrane proteins in native cellular membranes is critical to precisely reveal their structures in physiological conditions. However, it remains challenging for solid-state nuclear magnetic resonance (ssNMR) due to the low sensitivity and high complexity of ssNMR spectra of cellular membranes. Here, we present the structure determination of aquaporin Z (AqpZ) by ssNMR in Escherichia coli inner membranes. To enhance the signal sensitivity of AqpZ, we optimized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 75 publications
0
5
0
Order By: Relevance
“…More recently, the Yang group reported approaches for structure determination of membrane proteins in E. coli cellular inner membranes. , A “dual-media” expression approach and antibiotic treatment were employed to suppress the interference of background proteins, while signal sensitivity was effectively enhanced upon a high level of overexpression of aquaporin Z (AqpZ) and the removal of outer membrane components. Based on the high sensitivity and good resolution of the ssNMR multidimensional spectra, almost all residues in AqpZ were successfully assigned.…”
Section: Protein Structure Determination Using In-cell Nmrmentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, the Yang group reported approaches for structure determination of membrane proteins in E. coli cellular inner membranes. , A “dual-media” expression approach and antibiotic treatment were employed to suppress the interference of background proteins, while signal sensitivity was effectively enhanced upon a high level of overexpression of aquaporin Z (AqpZ) and the removal of outer membrane components. Based on the high sensitivity and good resolution of the ssNMR multidimensional spectra, almost all residues in AqpZ were successfully assigned.…”
Section: Protein Structure Determination Using In-cell Nmrmentioning
confidence: 99%
“…Based on the high sensitivity and good resolution of the ssNMR multidimensional spectra, almost all residues in AqpZ were successfully assigned. More than 1000 13 C– 13 C distance restraints were then obtained from 13 C– 13 C combined R2 n v -driven (CORD) spectra for structure calculation, and the 1.7-Å ssNMR structure of AqpZ in E. coli cellular inner membranes was determined based on the experimental distance restraints . This work provides a strategy for determining the structure of highly expressed membrane proteins in the cellular environment, while structure determination of proteins with lower expression levels is still hampered by the inherent low sensitivity of ssNMR.…”
Section: Protein Structure Determination Using In-cell Nmrmentioning
confidence: 99%
“…[10,33] Recently, all these strategies have been used in tandem to facilitate membrane-protein structure determination within native membrane extracts. [107] Given the difficulty of recombinantly producing biomolecules in eukaryotic cells without background labelling, [108] in-cell NMR studies attempting to investigate the structural aspects of molecules in such systems have sought to employ delivery systems. The idea of delivering exogenous molecules to cells is highly attractive as it permits to simultaneously ensure selective stable isotope labelling and exert control over the intercellular molecule concentration.…”
Section: Selective Stable Isotope Labelling Intercellular Biomolecule...mentioning
confidence: 99%
“…Subsequently, the Reif group used DNP-ssNMR (400 MHz/227 GHz), protein overexpression, amino acid selective-labelling, membrane extraction, and 3D carbon detected experiments to acquire inter-residue assignments (i, i-1) which revealed that the protein Mistic was membrane-embedded and structurally homogenous in E.coli. [54] The methods pioneered above were subsequently used to characterize a variety of bacterial membrane proteins, [107,129,130] with a shift to characterizing larger complexes like the pentameric 200 kDa β-barrel assembly machine (BAM), [131] the megadalton type IV secretion complex, [33] and more recently the 231 residue aquaporin 2. [107] In the case of the secretion complex, it was demonstrated that DNP-ssNMR was capable of detecting signals from highly dynamic segments that were previously poorly resolved by other structure elucidation techniques.…”
Section: Dnp-ssnmr To Study Macromolecular Assemblies In Bacterial Cellsmentioning
confidence: 99%
See 1 more Smart Citation